Polyamine conjugates of stigmasterol - Vida, Norbert; Svobodová, Hana; Rárová, Lucie; Drašar, Pavel; Saman, David; Cvačka, Josef; Wimmer, Zdeněk (Steroids, 2012)
Three new polyamine conjugates with stigmasterol [(3β,22E)-stigmasta-5,22-dien-3-ol] were synthesized and subjected to basic antimicrobial and cytotoxic tests. The conjugate derived from spermine, (3β,22E)-stigmasta-5,22-dien-3-yl 4(12-amino-4,9-diaza-dodecylamino)-4-oxobutanoate (5c), displayed considerable antimicrobial activity on Staphylococcus aureus at low concentration (50 μg mL(-1)). The cytotoxic activity was tested on cells of human T-lymfoblastic leukemia (IC(50)=35.8 ± 10.3 μM (5c) and IC(50)=35.9 ± 5.7 μM (5b)) and normal human fibroblasts (IC(50)=38.0 ± 2.8 μM (5c) and IC(50)=45.5 ± 1.9 μM (5b)). Conjugate 5a displayed no activity in both tests.
Keywords: molekulární konformace; Models, Molecular; Staphylococcus aureus; Molecular Conformation; Stigmasterol; Humans; Carboxylic Acids; Dose-Response Relationship, Drug; Antineoplastic Agents; kyseliny karboxylové; lidé; antibakteriální látky; molekulární modely; Drug Design; Chemical Phenomena; Anti-Bacterial Agents; racionální návrh léčiv; stigmasterol; nádorové buněčné linie; protinádorové látky; polyaminy; chemické jevy; vztah mezi dávkou a účinkem léčiva; Cell Line, Tumor; Polyamines